Japan and the European community: An uneasy partnership - Wilhelm Haferkamp (Intereconomics, 1981)
Bewildering advances of Japanese production into many fields of European industry are a cause of grave concern in the EC. Calls for protection are growing louder as a mixture of fear and impatience spreads throughout the Community. Wilhelm Haferkamp, EC Commissioner in charge of external trade relations, explains why trade war practices are no solution to the problem.
Keywords: 330; European Community